Folded monopole antenna with CSRRS for tri-band applications - Gangwar, AK.; Alam, MS. (International Journal of Engineering and Technology, 2018)
In this paper, a miniaturize folded monopole antenna with complementary split ring resonator (CSRR) is proposed for tri-band applications. In the design procedure of the antenna, first a single band monopole antenna is designed for 2.88 GHz. For design a single band to dual band, the both arms of the radiating element (i.e. Monopole) is folded then it is resonated at 2.68GHz and 5.15GHz resonance frequencies, the resonance of the lower frequency is based on length of the monopole and higher order resonance is excited due to its folding effect. In order to extend its resonances for tri-band operation, the two identical size CSRRs (one on the left and another on the right from the feed line) are placed on the ground plane of the edge of the folded monopole, thus the entire structure is resonated at 2.47 GHz, 3.46GHz and 4.36 GHz frequencies. A simplified equivalent circuit model is developed for understanding its electrical behavior. Therefore, the proposed antenna has been suitable for WLAN, WiMAX and C-band applica- tions.
Keywords: Tri-Band; CSRR; Monopole Antenna; Equivalent Circuit.